Clinical and laboratoristic strategy in late onset hypogonadism - Lombardo, Francesco; Lupini, Cristina; Meola, Antonella; Pallotti, Francesco; Gandini, Loredana; Lenzi, Andrea (Acta Biomedica Atenei Parmensis, 2010)
Aging in men is associated with a gradual and progressive decline in serum total testosterone concentrations as a result of primary testicular and secondary hypothalamic-pituitary dysfunction. Androgen secretion does not cease, it gradually decreases but usually continues at some level. A diagnosis of hypogonadism should rely on both symptoms and laboratory tests. Declining testosterone levels with age are primarily due to changes in the testes, which show decreases in the number of Leydig cells, the activity of enzymes that contribute to testosterone production, and the ability to increase testosterone production in response to gonadotropin stimulation. Physicians should also take note of symptoms indicatine age-related complaints. Validated questionnaires can be helpful. Administration of androgens appears to improve positive aspects of mood. Hypogonadism is also a risk factors for osteoporosis. Aging is associated with a reduction in sexual activity. T and DHT appear to be essential for development and maintenance of libido or sexual desire, and they probably have a direct effect on penile erections. Testosterone replacement therapy (TRT) affects nocturnal erections and penile rigidity in hypogonadal males. It is not known whether TRT will increase the risk of prostate cancer. The influence of T on prostate carcinogenesis and other prostate outcomes remains poorly defined. The aim of treatment for hypogonadism is to normalize serum testosterone levels and abolish symptoms or pathological states that are due to low testosterone levels. The exact target testosterone level is a matter of debate, but current recommendations advocate levels in the mid-lower normal adult range.